2005
DOI: 10.1007/s11010-005-2056-x
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan residue is essential for immunoreactivity of a diagnostically relevant peptide epitope of A. fumigatus

Abstract: The role of tryptophan (Trp17) in immunoreactivity of P1, the diagnostically relevant peptide from a major allergen/antigen of Aspergillus fumigatus, was evaluated by chemically modifying tryptophanyl residue of P1. In BIAcore kinetic studies, unmodified P1 showed a 100-fold higher binding with ABPA (Allergic Bronchopulmonary Aspergillosis) patients' IgG [KD (equilibrium dissociation constant) = 2.74 e(-8) +/- 0.13 M] than the controls' IgG (KD = 2.97 e(-6) +/- 0.14 M), whereas chemically-modified P1 showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…One of the earliest known and characterized allergen/antigen of Afu is Asp f1 with 85% of allergic aspergillosis patients showing IgE antibodies to Asp f1 (17,18,23-25). Asp f1 is a cytotoxic ribonuclease hindering its use for immunotherapy in a native form owing to the possible toxicities and IgE-mediated side effects.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest known and characterized allergen/antigen of Afu is Asp f1 with 85% of allergic aspergillosis patients showing IgE antibodies to Asp f1 (17,18,23-25). Asp f1 is a cytotoxic ribonuclease hindering its use for immunotherapy in a native form owing to the possible toxicities and IgE-mediated side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Using an assay with these proteins mutated at their residues important for IgE binding, they showed that the protein specifically lost its binding activity and exhibited reduced IgE induction in the immunized mice. Kamal et al (2005) described that the tryptophan residue is essential for immunoreactivity of a diagnostically relevant peptide epitope of A. fumigatus. The loss of specific IgG and IgE antibody binding of the modified protein by ELISA confirmed the critical role of tryptophan (Trp17) in the immunoreactivity of this protein.…”
Section: Solutionsmentioning
confidence: 99%